THE ORIENTATION OF VOCATIONAL EDUCATION AT STATE ISLAMIC SENIOR HIGH SCHOOL (MAN) 2 KULON PROGO IN SPECIAL REGION OF YOGYAKARTA - Muhamad Wahib Jamil; Abdul Munip; Zainal Arifin (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
The background of this study is that vocational education places greater emphasis on the link and match pattern. This pattern is more oriented toward the ideology of liberalism or neoliberalism that supports capitalism. Substantially, Islamic education has an orientation to realize the concept of insan kamil. Therefore, it becomes important to conduct in-depth research on the implementation of madrasah education based on religious humanism that is integrated as a defense against the influence of liberalism, neoliberalism, and capitalism. The aim is to provide an in-depth analysis of the orientation of vocational education. The method used is a qualitative goal-free evaluation approach with data collection through documentation techniques, observation, interviews, and in-depth discussions with subject research in State Islamic Senior High School (MAN) 2 Kulon Progo in Special Region of Yogyakarta. Research Results: this study found that the implementation of education in the vocational program at Madrasah Aliyah is very good. The direction of vocational education in madrasahs is not necessarily based on liberalism-neoliberalism, capitalist domination, or market demand dominance; rather, the values of religious humanist education and the internalization of Islamic values are very dominant and become the educational values. Religious humanist education is realized through an integration-interconnection model in the educational process. Conclusion: The educational model at State Islamic Senior High School (MAN) 2 Kulon Progo, integrating religious values and skills, is an alternative for vocational education. This strategy can be a trendsetter for other vocational education institutions. Therefore, policymakers can position religious values education as a foundation in vocational education policies.